2012
DOI: 10.1007/s10815-012-9762-6
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone levels on the hCG day and outcomes in vitro fertilization in women with polycystic ovary syndrome

Abstract: Background The purpose of this study was to determine the incidence of premature luteinization in patients with polycystic ovary syndrome and compared the main determinants of success in in-vitro fertilization in PCOS patients with and without premature luteinization. Methods Retrospective analysis of 180 PCOS women of Chinese Han origin with infertility who underwent controlled ovarian hyperstimulation (COH) with an exogenous gonadotropin/GnRH antagonist protocol. Hormone levels on the hCG day and IVF outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…27 Patients with PCOS tend to show ovarian hyperresponse and have more oocytes retrieved, with many patients developing OHSS. 28,29 Several studies were carried out to compare the miRNA expression between patients with PCOS and normal individuals. After small RNA sequencing of cumulus granulosa cells from PCOS and controls were performed, a total of 59 known miRNA were identified that were differentially expressed in PCOS granulosa cells, including an increase in 21 miRNAs and a decrease in 38 miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…27 Patients with PCOS tend to show ovarian hyperresponse and have more oocytes retrieved, with many patients developing OHSS. 28,29 Several studies were carried out to compare the miRNA expression between patients with PCOS and normal individuals. After small RNA sequencing of cumulus granulosa cells from PCOS and controls were performed, a total of 59 known miRNA were identified that were differentially expressed in PCOS granulosa cells, including an increase in 21 miRNAs and a decrease in 38 miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kolibianakis et al [166] in a subsequent review demonstrated a significant adverse effect on PRs in GnRH antagonist cycles and the large 2013 systematic review and meta-analysis of more than 55,000 cycles from 63 publications, confirmed that progesterone rise on the day of hCG, decreases the probability of pregnancy in fresh IVF cycles [1]. Since then, the scientific dialog on the matter continues with various cut-offs, and even though there is some scars evidence of improved clinical results of preovulatory progesterone rise [7,12,167], or conclusions of no significant effect [122,124,126,[168][169][170], there are also clear reports of unfavorable results on CPR and LBR [22,24,52,96,99,112,116,117,129,131,137,145,151]. Venetis et al [133] demonstrated in a retrospective study that multivariable analysis taking into consideration multiple confounding factors revealed statistically significant decrease in LBR for cycles with progesterone rise on trigger day whereas bivariate analysis failed to do so in the same cohort.…”
Section: Success Ratesmentioning
confidence: 96%
“…Prematür lüteinizasyon gelişen olgularda, PL gelişmemiş olgulara göre toplanan oosit sayısı ve fertilizasyon oranının daha yüksek olduğunu, fakat implantasyon ve klinik gebelik oranlarının ise anlamlı bir fark göstermediğini bildirmişlerdir. [15] Bizim çalışmamızda antagonist grubunda PL insidansı 1 ng/mL eşik değeri için %34 iken; 1.5 ng/mL eşik değeri için ise %6.9 idi. Prematür lüteinizasyon insidansı, kabul edilmiş net bir tanım olmamasından ötürü %13-71 arasında değişmektedir.…”
Section: Koh-icsiunclassified